2007
DOI: 10.1016/j.cardiores.2007.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Swimming reduces the severity of atherosclerosis in apolipoprotein E deficient mice by antioxidant effects

Abstract: Exercise training, in which the load did not affect energy metabolism efficacy of the heart, suppressed atherosclerosis by antioxidant effects via the vascular NO system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 47 publications
4
56
0
1
Order By: Relevance
“…Previous studies have shown that exercise training, such as on a treadmill and swimming, reduced atherosclerotic lesion formation and neointimal growth after carotid injury in mice models [11][12][13][14][15][16][17][18] ; however, such unpleasant exercise may be forced under stressful conditions with disruption of the normal diurnal rhythm [6][7][8][9] . In contrast, voluntary running exercise can be performed to assess the underlying mechanisms by which Levels of aortic mRNA expression of CD68, CD4, and CD11c were measured using real-time PCR in the STD (n 5), HFD (n 5), and HFD Ex (n 5) groups at 18 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that exercise training, such as on a treadmill and swimming, reduced atherosclerotic lesion formation and neointimal growth after carotid injury in mice models [11][12][13][14][15][16][17][18] ; however, such unpleasant exercise may be forced under stressful conditions with disruption of the normal diurnal rhythm [6][7][8][9] . In contrast, voluntary running exercise can be performed to assess the underlying mechanisms by which Levels of aortic mRNA expression of CD68, CD4, and CD11c were measured using real-time PCR in the STD (n 5), HFD (n 5), and HFD Ex (n 5) groups at 18 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…Kishimoto et al reported that NO and antioxidants may play an important role in the effects of exercise 13,18) . In addition, the vascular response to acetylcholine is related to an increase in NO bioavailability as a result of the upregulation of the antioxidant defense system 31) .…”
Section: Discussionmentioning
confidence: 99%
“…87 ApoE-deficient mice undergoing exercise training were recently found to exhibit a decreased susceptibility to atherosclerotic disease. 88 Interestingly, the protective effects were attributed to a reduction in ROS. 88 In another study, physical activity was shown to increase the production and circulating numbers of EPCs in mice.…”
Section: Physical Activitymentioning
confidence: 99%
“…88 Interestingly, the protective effects were attributed to a reduction in ROS. 88 In another study, physical activity was shown to increase the production and circulating numbers of EPCs in mice. 89 As described previously, EPCs are being investigated as an important component of endothelial regeneration and compensatory angiogenesis, functioning to counteract and protect the vascular wall from inflammatory cytokines.…”
Section: Physical Activitymentioning
confidence: 99%
“…To this end, long-term exercise intervention has been shown to reduce the severity of atherosclerosis (31), to stabilize vascular lesion (36), and to lessen post-injury neointima growth (38). The mechanism underlying these adaptive changes is believed to be governed by high wall shear rates occurring during exercise.…”
mentioning
confidence: 99%